Judicial Authority and Term Extension: A Sulṭah al-Qaḍā’iyyah Perspective on Constitutional Court Decision No. 112/PUU-XX/2022 - Marhalim, M; Siregar, Rahmad Efendi Amin; Reza, T. Surya (MAQASIDI: Jurnal Syariah dan Hukum, 2025)
Constitutional Court Decision No. 112/PUU-XX/2022, which extended the term of office of the Head of the Corruption Eradication Commission (KPK) from four to five years, has sparked public debate. On the one hand, the longer term is viewed as a means to ensure the effectiveness and continuity of anti-corruption efforts. On the other hand, many parties argue that this change opens the door to political interference, potentially compromising the independence of the institution and raising concerns regarding the principle of checks and balances. This research aims to analyze the decision from the perspective of Sulṭah al-Qaḍā’iyyah, the concept of judicial authority in Islamic law, which is grounded in the principles of justice (al-‘adālah), deliberation (shūrā), and public interest (al-maṣlaḥah al-‘āmmah). The study employs a normative juridical approach and qualitative methodology based on a literature review. The findings suggest that Constitutional Court Decision No. 112/PUU-XX/2022 has exceeded the Court’s role as a negative legislator, as it is seen to have created a new legal norm without following the formal legislative process. Although the decision is justified by the argument that a five-year term is needed to strengthen the independence, effectiveness, and stability of KPK leadership, from the perspective of Islamic law, such action may be ethically and substantively flawed if it disregards public participation and leads to social unrest. Therefore, this decision should be reconsidered not only from a constitutional standpoint but also in light of the substantive values of justice within the framework of maqāṣid al-sharī‘ah.